Behaviorally-based couple therapies reduce emotional arousal during couple conflict. (September 2015) - Baucom, Brian R.; Sheng, Elisa; Christensen, Andrew; Georgiou, Panayiotis G.; Narayanan, Shrikanth S.; Atkins, David C.
Abstract: Emotional arousal during relationship conflict is a major target for intervention in couple therapies. The current study examines changes in conflict-related emotional arousal in 104 couples that participated in a randomized clinical trial of two behaviorally-based couple therapies. Emotional arousal is measured using mean fundamental frequency of spouse's speech, and changes in emotional arousal from pre-to post-therapy are examined using multilevel models. Overall emotional arousal, the rate of increase in emotional arousal at the beginning of conflict, and the duration of emotional arousal declined for all couples. Reductions in overall arousal were stronger for TBCT wives than for IBCT wives but not significantly different for IBCT and TBCT husbands. Reductions in the rate of initial arousal were larger for TBCT couples than IBCT couples. Reductions in duration were larger for IBCT couples than TBCT couples. These findings suggest that both therapies can reduce emotional arousal, but that the two therapies create different kinds of change in emotional arousal. Highlights: Emotional reactivity operationalized using basic and applied research on emotion. Behaviorally based couple therapies reduce emotional reactivity during conflict. Findings integrated within common principles approach to enhance applicability. Provides recommendations for adding specificity to the common principles approach.